Occurrence of Bovine Viral Diarrhea (BVDV) and Bovine Infectious Rhinotracheitis (IBR) Virus Infections in Buffaloes in Pernambuco state - Brazil - Soares, Larice Bruna Ferreira; Silva, Bruno Pajeú e; Borges, Jonas de Melo; Oliveira, Júnior Mário Baltazar de; Macêdo, Allison Alves de; Aragão, Breno Bezerra; Nascimento, Sérgio Alves do; Junior, José Wilton Pinheiro (Acta Scientiae Veterinariae, 2017)
Background: Buffaloes are susceptible to viral infections, often associated with pathologies of importance in cattle breeding. Among the numerous infectious diseases, Bovine Viral Diarrhea (BVDV) and Bovine Infectious Rhinotracheitis (IBR) have a negative impact on buffalo creations. This study aimed to detect the occurrence of bovine viral diarrhea virus (BVDV) and infectious bovine rhinotracheitis (IBR) virus infections in buffaloes in Pernambuco state, Brazil. Materials, Methods & Results: For this purpose, serum samples were obtained from 244 buffaloes on eight properties distributed in six municipalities. The search for anti-BVDV and -bovine herpesvirus type-1 (BoHV-1) antibodies was performed using the virus neutralization technique. To analyze the association between the serological status of BoHV-1 infection and aspects of hygienic-sanitary and reproductive management, an investigative questionnaire with objective questions was used. In total, 97.9% (239/244) of buffaloes had anti-BVDV antibodies and 56.1% (137/244) had anti-BoHV-1 antibodies. Co-infection was observed in 55.3% (135/244) of buffaloes. The distribution of antibody occurrence in buffaloes by properties ranged from 90.5% to 100.0% for BVDV and from 4.8% to 100% for BoHV-1. It was not possible to perform an association analysis for BVDV infection; however, in that for BoHV-1 infection, the following variables exhibited a significant association: an extensive breeding system (P < 0.001), open herd (P = 0.029), lack of reproductive rest (P = 0.029), natural mating in females with reproductive disorders (P < 0.001), exploration type (P = 0.0014), presence of wild animals (P < 0.001), and lack of cleaning facilities (P = 0.008). Discussion: The occurrence of anti-BVDV antibodies in this study was 97.9% this was higher than those reported in other country’s regions. The results of the present study demonstrate a high occurrence of anti-BVDV antibodies in each of the properties in Pernambuco state, demonstrating that the animals have contact with infection sources, due to the large number of positive animals. Indeed, it is likely that there is at least one PI animal in every herd. It was observed that 100% of the properties possessed at least one positive animal. The high number of positive animal properties may be related to the absence of biosecurity measures; a subclinical BVDV infection can occur which the owners cannot identify it, as it is not common the adoption of a reproductive program in the region. The occurrence of the anti-BoHV-1 antibody in this study was 56.1%. In other states, both lower and higher prevalences were reported compared to this study. The high number of properties with positive animals may be related to several factors, including the ability of the virus to remain latent, thus introducing a single animal infected with BoHV-1 sufficient for infection spread and perpetuation in buffaloes. It is believed that the introduction of infected animals and the lack of disease knowledge by the producers may have been responsible for the agent’s introduction and maintenance in the herds. In conclusion, BVDV and IBR virus infections occur in buffaloes in Pernambuco state. Thus, it is suggested that prophylactic measures, including routine diagnosis, reproductive animal control, and strict health care, such as employing cleaning facilities, avoiding contact with neighboring herds, acquiring animals with a negative diagnosis and using an artificial insemination program should be implemented at each property to reduce the reproductive losses caused by these infections.